2020
DOI: 10.1080/24740527.2020.1785854
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of treatment needs in interstitial cystitis/bladder pain syndrome: Implications for intervention

Abstract: Background: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a debilitating condition carrying substantial psychosocial burden. Psychological treatment for IC/BPS is little studied, and there are barriers to its use in clinical management. Whether psychological treatments benefit patients with IC/BPS is unclear and we do not know whether such treatments would meet patient needs. Aims: Incorporating patient-reported needs and acknowledging diversity in pain experiences can inform patient-centered interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(61 citation statements)
references
References 51 publications
0
48
2
2
Order By: Relevance
“…Future studies will be required to gain insight into the perspectives of a more diverse group of patients with more severe symptoms. Our sample size was small, and therefore may have differing demographics compared to the general population of patients with IC/BPS, but is comparable to prior focus group studies on urinary symptoms [ 15 , 17 ]. Additionally, our fifth focus group revealed that we had reached saturation of themes by the fourth focus group suggesting that additional focus groups would not have added to the themes identified.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Future studies will be required to gain insight into the perspectives of a more diverse group of patients with more severe symptoms. Our sample size was small, and therefore may have differing demographics compared to the general population of patients with IC/BPS, but is comparable to prior focus group studies on urinary symptoms [ 15 , 17 ]. Additionally, our fifth focus group revealed that we had reached saturation of themes by the fourth focus group suggesting that additional focus groups would not have added to the themes identified.…”
Section: Discussionmentioning
confidence: 80%
“…Chen et al [ 16 ] described the frustrations of living with IC/BPS and reviewed some specific culturally based coping strategies, such as Chinese herbal supplements or drinking warm water. Other qualitative research described the psychological impact of IC/BPS and highlighted the need for mental health services in an integrated care model [ 17 ]. Although these studies described the experience of living with IC/BPS, there is a relative lack of data regarding how patients weigh various factors when choosing a treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…(5) prevention methods; (6) barriers to maintaining positive change; and (7) symptom improvement. These kidney-stone specific questions were developed by collaboration between the co-authors and the Vanderbilt Qualitative research core, based on previous qualitative research experience, with an aim to stimulate open-ended discussion [17]. After setting the stage by inquiring about time of first kidney stone diagnosis, initial open-ended questions designed to elicit broad responses were posed.…”
Section: Patient Interviewsmentioning
confidence: 99%
“…It is therefore important to understand how such interventions may need to be tailored according to gender-based needs. Our recent study exploring women's experience of IC/BPS found that symptom severity was significantly associated with depression and that there was a reciprocal relationship between psychosocial stress and symptom exacerbations ( 17 ). Key qualitative themes included the experience of invalidation from loved ones and healthcare providers, social withdrawal, isolation, and a perceived lack of control over symptoms ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using qualitative analysis provides an in-depth assessment of patient experiences necessary to understand the impact and perceived needs in IC/BPS due to the limited existing research. We sought to highlight salient differences between genders informed by our previous qualitative assessment of women's experience of IC/BPS ( 17 ), by replicating methods and comparing findings by gender.…”
Section: Introductionmentioning
confidence: 99%